The satisfaction level of medical tourism in Putra Specialist Hospital (Melaka) Sdn Bhd / Nazmi Hasif Sulaiman and Nur Hamizah Amran - Sulaiman, Nazmi Hasif; Amran, Nur Hamizah (Faculty of Business and Management, 2016)
This paper reviews about the medical tourism industry in Malaysia. It reviews about factors that will affect patient’s satisfaction towards the service in the country. Patient’s satisfaction is important as it influenced future decisions for patients to return back as repeated customers and also increase the chances in obtaining new customers. In the first chapter, there will be a brief discussion on the background of the study, the problem statement, the research objectives and questions and also the basic hypothesis of the study. The first chapter focuses on giving the primary details. Here, the researchers try to determine the major factors that could influence the satisfaction level in the medical tourism industry. Moving forward, there will be an elaborate discussion on the factors that will affect the satisfaction level of medical tourism. The factors that were identified is cost, perceived value and promotion. In this chapter the researcher will explained how these factors can increase patient’s satisfaction level of medical tourism services. Next, there will be a discussion of the findings that were obtained through the distribution of questionnaires to foreign patients in Putra Specialist Hospital. The will be an analysis that will determine the main factors that would affect satisfaction level the most. At the end of this chapter, there will be a full discussion of data analysis of the study. From the study done, the researcher finds out that the most important factor that affect satisfaction level in Putra Specialist Hospital is the perceived value factor Finally, at the end of the chapter, there will be a stated conclusion of the study and some recommendations to improve the findings of the study.